2014
DOI: 10.1590/1678-69712014/administracao.v15n3p21-41
|View full text |Cite
|
Sign up to set email alerts
|

Cooperar para sobreviver e crescer: análise da rede de cooperação redemac

Abstract: O alinhamento dos conceitos de cooperação em associações de empresas que buscam, por meio de objetivos comuns e estratégias coletivas, alcançar vantagens competitivas sustentáveis em longo prazo, como base nos benefícios e resultados da rede, é tema central desta pesquisa. Para fundamentar o referencial teórico exposto, buscou-se a literatura com base nos seguintes autores: Human e Provan (1997), Ebers e Jarillo (1998), Balestrin e Verschoore (2008), Powel (1998), Jarillo (1998), Castells (2012), Provan, Fish … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…Another report underlines that the cooperative provides members with greater competitiveness in the sector, as shown by C2 "...as the producer is part of a market where there is great competition, and when you are alone things become more difficult..." and C5 corroborates "First, I think this possibility of participating in a bidding process, where many cars are needed and I alone couldn't manage this, the group becomes stronger and more competitive...". Competitiveness was also identified previously in the study by Feijó and Zuquetto (2014) as a variable motivating cooperation between firms.…”
Section: Benefitssupporting
confidence: 64%
See 2 more Smart Citations
“…Another report underlines that the cooperative provides members with greater competitiveness in the sector, as shown by C2 "...as the producer is part of a market where there is great competition, and when you are alone things become more difficult..." and C5 corroborates "First, I think this possibility of participating in a bidding process, where many cars are needed and I alone couldn't manage this, the group becomes stronger and more competitive...". Competitiveness was also identified previously in the study by Feijó and Zuquetto (2014) as a variable motivating cooperation between firms.…”
Section: Benefitssupporting
confidence: 64%
“…Goel and Roessl (2015) concluded that respect for the individuality of each firm, in relation to its history, tradition and culture, is of major importance, even when they use common norms in the cooperation. Feijó and Zuquetto (2014) found that the benefits obtained by firms through cooperation were the opportunity to exchange information with other firms, cost reduction, greater negotiating power with suppliers and becoming more competitive in the sector.…”
Section: Motivations For Cooperation Between Firmsmentioning
confidence: 99%
See 1 more Smart Citation